Pendampingan Digitalisasi UMKM dengan Pelatihan AI dan Evaluasi Analisis Pohon Masalah di Bojonegoro - Kurniawan Indra Jaya; Andi Mulyanti Suhartini; Nurul Jariyatin; Devi Septiani (SEWAGATI: Jurnal Pengabdian kepada Masyarakat, 2026)
Usaha Mikro Kecil Menengah (UMKM/Micro, Small, and Medium Enterprises) in Bojonegoro have experienced significant development over time, which requires entrepreneurs to continue to develop and innovate. This Community Service activity aims to better prepare UMKM for digital adoption, particularly Generative AI adoption. The primary objective is to identify issues that arise when using digital technology, such as the use of Generative AI for UMKM businesses. The implementation method used for this community service is direct assistance to 5 UMKM and mapping problems using Problem Tree Analysis. The findings of community service problems in UMKM are based on a problem tree analysis, such as constraints on technical, economic, and human resources aspects such as difficult to understand application language, paid applications, and UMKM unfamiliarity with digital technology. Action plans or solutions that can be implemented include ongoing mentoring for UMKM, free Generative AI optimization, and familiarization of UMKM to utilize digital technology.